Methodology Of Communication Culture Development In Primary Education Students - Khayrullayeva is Nilufarkhan Azamjon's Qizi (Zien Journals, 2024)
This article presents ideas on the development of communication culture in English among students of primary education.
Keywords: Pedagogy; innovation; communication; culture